ELECTRONIC DOCUMENTS AS ELECTRONIC EVIDENCE - Varbanova, Gergana (International Journal of Law in Changing World, 2025)
The development of technology has led to the fact that a large part of the disputes has transcended national borders and acquired a cross-border character. This requires the study of electronic evidence, in particular electronic documents, as a qualitatively new legal phenomenon, which has its own independent regulation at national and supranational level. In order to understand the concept of "electronic document", a comparison will be made with the conventional, written document, indicating the similarities and differences between the two legal phenomena, as well as the peculiarities inherent only to electronic documents. The article explores the concept of the electronic evidence in conflict resolution through a mixed-methods approach combining systematic literature analysis and comparative case studies. The legal definition of an electronic document is analyzed. Author also concludes on the necessity of a rethinking of the theory of physical evidence in the context of electronic documents. _____ DOCUMENTOS ELECTRÓNICOS COMO PRUEBA ELECTRÓNICA El desarrollo tecnológico ha llevado a que gran parte de las controversias trasciendan las fronteras nacionales y adquieran un carácter transfronterizo. Esto exige el estudio de la prueba electrónica, en particular de los documentos electrónicos, como un fenómeno jurídico cualitativamente nuevo, con su propia regulación independiente a nivel nacional y supranacional. Para comprender el concepto de "documento electrónico", se realizará una comparación con el documento escrito convencional, indicando las similitudes y diferencias entre ambos fenómenos jurídicos, así como las peculiaridades inherentes únicamente a los documentos electrónicos. El artículo explora el concepto de prueba electrónica en la resolución de conflictos mediante un enfoque de métodos mixtos que combina el análisis sistemático de la literatura y estudios de casos comparativos. Se analiza la definición legal de documento electrónico. El autor también concluye sobre la necesidad de replantear la teoría de la prueba física en el contexto de los documentos electrónicos. ______ 电子文件作为电子证据 技术的发展导致大量争议跨越国界，并具有跨境特征。这需要研究电子证据，尤其是电子文件，作为一种全新的法律现象，在国家和超国家层面拥有其独立的规制。为了理解“电子文件”的概念，本文将与传统的书面文件进行比较，指出这两种法律现象之间的异同，以及电子文件所固有的特性。本文采用系统文献分析和比较案例研究相结合的混合方法，探讨电子证据在冲突解决中的概念。分析了电子文件的法律定义。作者还总结了在电子文件背景下重新思考物证理论的必要性。